Investigating Malaysian distance learners’ conceptions of their learning styles in learning English - Thang, Siew Ming (Penerbit UKM, 2003)
Research into the effectiveness of distance learning content courses has been undertaken in the Malaysian context, but so far, very little research has been carried out on distance language learning courses. This study is an attempt to rectify the lack of research into the learning needs of Malaysian distance language learners. The paper investigates the conceptions of learning styles in learning English as a Second Language (ESL) of Malaysian distance learners of a dual-mode public university. It attempts to provide insights that will help in designing a more appropriate ESL programme for these students and, possibly, for others in similar contexts. Willing’s questionnaire that drew upon the work of Witkin and Goodenough (1981) and Kolb’s model (1976) was used in this study. Factor analysis completed with the use of SPSS (Version 9) was used to identify learning styles groups. The influences of the differences in modes and proficiency levels on the characteristics of the members of each 'learning style group' were studied statistically. The main finding was that the distance learners, especially High Proficiency Learners, seemed more oriented to learning English independently than the on-campus learners. This was attributed to the inclination among more 'mobile' learners (both on-campus and distance learners) to opt for learning styles they considered more appropriate to their mode of learning.